Two-site assay of human α1-fetoprotein using125I-labelled monoclonal antibodies. Issue 10 (October 1981) - Weeks, Ian; Kemp, Heather A.; Woodhead, J. Stuart
Abstract : Monoclonal antibodies to human α1 -ietoprotein (AFP) have been compared with a conventionally produced antiserum using radioimmunoassay and two-site immunoradiometric techniques. A low-affinity antibody, which proved inadequate for use in a radioimmunoassay, gave asatisfactory dose-response Curve in a rapid two-site assay. A higher-affinity antibody yielded a simple, rapid, and sensitive two-site assay suitable for routine measurement of serum AFP.